Исследование влияния ионов железа на качество розовых столових виноматериалов - Билько, Марина Владимировна; Гречко, Нина Яковлевна (My University, 2014)
Исследовано влияния ионов железа и их форм на окислительно-восстановительное состояние и цветовые характеристики розовых столовых виноматериалов. Установлено, что в процессе окисления виноматериалов происходит перераспределение форм железа, в основном ионы Fe (II) переходят в Fe (III). С увеличением содержания железа увеличивается процент снижения содержания фенольных и красящих веществ, повышается степень окисленности виноматериалов. The effect of iron ions and their forms on the oxidation-reduction condition and the colour characteristics of rose dry wine, phenolic and anthocyanins content were researched. The redistribution of iron form in the wine in the oxidation process was established. The ions Fe (II) pass into Fe (III). Upon that phenolic and anthocyanins content reduce in rose dry wine. Activating effect of oxidation of the iron content up to 15 mg/dm3 was established. It was exposed that increasing concentration of iron increases the degree of oxidation This fact is indicated by the change of redox characteristics of dry rose wine. The ways to improve the quality of dry rose wine are: to protect it from oxidation, to watch over the level of iron and in the case of its limit-exceeding – to conduct the demetallizatoin.
Keywords: розовые сухие виноматериалы; фенольные вещества; красящие вещества; формы железа; окисление; dry rose wine; phenolic substances; anthocyanins; forms of iron; oxidation; кафедра біотехнології продуктів бродіння і виноробства